Validation of a Computer-Administered Version of the Digits-in-Noise Test for Hearing Screening in the United States - Folmer, Robert L. (J Am Acad Audiol, 2017)
BACKGROUND: The sooner people receive treatment for hearing loss, the quicker they are able to recognize speech and to master hearing aid technology. Unfortunately, a majority of people with hearing loss wait until their impairments have progressed from moderate to severe levels before seeking auditory rehabilitation. In order to increase the number of individuals with hearing loss who pursue and receive auditory rehabilitation, it is necessary to improve methods for identifying and informing these people via widely accessible hearing screening procedures. Screening for hearing loss is the first in a chain of events that must take place in order to increase the number of patients who enter the hearing healthcare system. New methods for hearing screening should be readily accessible through a common medium (e.g, telephone or computer) and should be relatively easy and quick for people to self-administer. PURPOSE: The purpose of this study was to assess a digits-in-noise (DIN) hearing screening test that was delivered via personal computer. RESEARCH DESIGN: Participants completed the Hearing Handicap Inventory for Adults (HHIA) questionnaire, audiometric testing in a sound booth, and computerized DIN testing. During the DIN test, sequences of 3 spoken digits were presented in noise via headphones at varying signal-to-noise ratios. Participants entered each three-digit sequence they heard using an on-screen keypad. STUDY SAMPLE: Forty adults (16 females, 24 males) participated in the study, 20 of whom had normal hearing and 20 with hearing loss (pure-tone average [PTA] thresholds for 0.5, 1, 2, and 4 kHz >25 dB HL). DATA COLLECTION AND ANALYSIS: DIN signal-to-noise (SNR) and PTA data were analyzed and compared for each ear tested. Receiver operating characteristic (ROC) curves based on these data were plotted. A measure of overall accuracy of a screening test is the area under the receiver operating characteristic curve (AUC). This measures the average true positive rate across false positives at varying DIN SNR cut-offs. Larger values of the AUC indicate, on average, more accurate screening tests. HHIA responses were analyzed and compared to PTA and DIN SNR results using Pearson correlation statistics. RESULTS: HHIA scores were positively correlated with audiometric PTA and DIN SNR results (p<0.001 for all correlations). For a hearing loss criterion of one or more frequencies from 0.25 to 8 kHz > 25 dB HL, the area under the receiver operating characteristic curve (AUC) for the DIN test was 0.95. When a criterion of hearing loss was set at one or more frequencies from 0.25 to 8 kHz >20 dB HL, the AUC for the DIN test was 0.96. CONCLUSIONS: The computer version of the DIN test demonstrated excellent sensitivity and specificity for our sample of 40 participants. AUC results (≥0.95) suggest that this DIN test administered via computer should be very useful for adult hearing screening.